Nanocrystalline nickel oxide target material and application thereof in transparent conductive film
Through the combination of two-step hydrothermal method and surfactant, nanocrystalline nickel oxide targets were prepared, which solved the problem of insufficient conductivity and transparency of traditional nickel oxide targets in transparent conductive films, and achieved better conductivity and transparency.
Patent Information
- Application Number
- CN202411801599.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-04-11
AI Technical Summary
Traditional nickel oxide targets have poor electrical conductivity and transparency when used in transparent conductive films.
The nanocrystalline nickel oxide target was prepared by two-step hydrothermal method. By coating the alumina on the surface of nickel oxide and using the mutual cooperation of anionic and cationic surfactants, the uniformity of the target grains and uniform adsorption of alumina were improved.
It significantly improves the conductivity and transparency of the transparent conductive film, reduces phase separation under high-temperature sintering, and reduces the influence of adverse phases.
Smart Images

Figure BDA0005178178100000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plate manufacturing, and in particular to a nanocrystalline nickel oxide target material and an application thereof in a transparent conductive film. Background Art
[0002] Transparent conductive films are widely used in optoelectronic fields such as solar cells, touch screens, and displays. Their performance directly affects the photoelectric conversion efficiency and application range of the products. At present, there are many challenges in the preparation technology of transparent conductive films, especially the purity and microstructure of the target material have a decisive influence on the performance of the film.
[0003] Patent technical document CN201910683264.4 discloses a nickel oxide tungsten target and a preparation method thereof. The specific preparation steps of the nickel oxide tungsten target are as follows: grind nickel oxide to obtain nickel oxide particles; activate tungsten oxide and grind it to obtain activated tungsten oxide particles; mix the nickel oxide particles and activated tungsten oxide particles evenly, press them to obtain a blank; sinter the blank to obtain a nickel oxide tungsten target. The invention establishes the relationship between particle size and molar ratio to obtain a nickel oxide tungsten target for electrochromism with uniform composition and high density. It has a certain conductivity and can use a DC or medium frequency power supply. However, when it is used to prepare a conductive transparent film, its conductivity and transparency still need to be further improved. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide a nanocrystalline nickel oxide target and its application in a transparent conductive film, so as to solve the problem of poor conductivity and transparency of a conventional nickel oxide target when used in a transparent conductive film.
[0005] Based on the above purpose, the present invention provides a nanocrystalline nickel oxide target comprising the following preparation steps:
[0006] (1) dissolving nickel nitrate hexahydrate in deionized water, then adding hexadecyltrimethylammonium bromide and PVP, adjusting the pH to 9-10, transferring it to a reaction kettle, reacting at 160-180° C. for 8-12 hours, filtering, washing, and drying at 80-120° C. to obtain nickel oxide powder;
[0007] (2) dissolving aluminum nitrate nonahydrate in deionized water, then adding sodium dodecyl sulfate and PVP, and adjusting the pH to 9-10, then adding nickel oxide powder to the system, transferring it to a reactor, reacting at 160-180° C. for 8-12 hours, filtering, washing, and drying at 80-120° C. to obtain a composite powder;
[0008] (3) Pre-sintering the composite powder in an argon atmosphere, and then keeping the temperature at 1100-1300°C for 2 hours;
[0009] (4) The sintered composite powder is subjected to hot isostatic pressing to obtain a nanocrystalline nickel oxide target.
[0010] Preferably, the weight ratio of nickel nitrate hexahydrate, deionized water, hexadecyltrimethylammonium bromide and PVP in step (1) is 10-15:200-300:0.01-0.02:0.05-0.1.
[0011] Preferably, the purity of the nickel nitrate hexahydrate in step (1) is not less than 99.99%.
[0012] Preferably, the weight ratio of aluminum nitrate nonahydrate, deionized water, sodium dodecyl sulfate and PVP in step (2) is 100-150:300-500:0.1-0.2:0.5-1.
[0013] Preferably, the purity of the aluminum nitrate nonahydrate in step (2) is not less than 99.99%.
[0014] Preferably, the weight ratio of nickel nitrate hexahydrate to nickel oxide powder in step (2) is 1:5.
[0015] Preferably, the pre-sintering temperature in step (3) is 300-400° C. and the time is 2 hours.
[0016] Preferably, the parameters of the hot isostatic pressing treatment in step (4) are: temperature of 1100-1200° C., pressure of 1200-1400 MPa, and time of 2-3 h.
[0017] Preferably, the pH is adjusted using sodium hydroxide.
[0018] Furthermore, the present invention also provides an application of a nanocrystalline nickel oxide target material, which is applied to prepare a transparent conductive film.
[0019] Beneficial effects of the present invention:
[0020] The present invention prepares nickel oxide powder by a hydrothermal method first, and then coats aluminum oxide on the surface of nickel oxide by a hydrothermal method to form a composite powder, so that aluminum oxide is evenly distributed on the surface of nickel oxide powder, reduces phase separation under high temperature sintering, and makes the film obtained after sputtering have better conductivity and transparency.
[0021] The present invention further improves the uniformity of the target grains by using anionic and cationic surfactants to cooperate with each other, and the electrostatic effect between them enables aluminum oxide to be uniformly and stably adsorbed on the surface of nickel oxide powder, thereby making the film have better conductivity and transparency.
[0022] The present invention adopts a two-step hydrothermal method and the cooperation of anionic and cationic surfactants to enable aluminum oxide to be uniformly and stably adsorbed on the surface of nickel oxide powder, thereby reducing phase separation at high temperature and the influence of undesirable phases, and ultimately making the film have excellent conductivity and transparency. DETAILED DESCRIPTION
[0023] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0024] Example 1: A nanocrystalline nickel oxide target material is specifically prepared as follows:
[0025] (1) dissolving 100 g of nickel nitrate hexahydrate in 300 g of deionized water, then adding 0.1 g of hexadecyltrimethylammonium bromide and 0.5 g of PVP, and adjusting the pH to 9, transferring the mixture to a reactor, reacting at 160° C. for 8 h, filtering, washing, and drying at 80° C. to obtain nickel oxide powder;
[0026] (2) dissolving 10 g of aluminum nitrate nonahydrate in 200 g of deionized water, then adding 0.01 g of sodium dodecyl sulfate and 0.05 g of PVP, and adjusting the pH to 9, then adding 50 g of nickel oxide powder to the system, transferring it to a reactor, reacting at 160° C. for 8 h, filtering, washing, and drying at 80° C. to obtain a composite powder;
[0027] (3) In an argon atmosphere, the composite powder was kept at 300°C for 2 h, and then kept at 1100°C for 2 h;
[0028] (4) The sintered composite powder is subjected to hot isostatic pressing to obtain a nanocrystalline nickel oxide target; wherein the parameters of the hot isostatic pressing treatment are: temperature 1100° C., pressure 1200 MPa, and time 2 h.
[0029] Example 2: A nanocrystalline nickel oxide target material is specifically prepared as follows:
[0030] (1) dissolving 125 g of nickel nitrate hexahydrate in 400 g of deionized water, then adding 0.15 g of hexadecyltrimethylammonium bromide and 0.75 g of PVP, and adjusting the pH to 9-10, transferring the mixture to a reactor, reacting the mixture at 170° C. for 10 h, filtering, washing, and drying the mixture at 80-120° C. to obtain nickel oxide powder;
[0031] (2) 13 g of aluminum nitrate nonahydrate was dissolved in 250 g of deionized water, followed by the addition of 0.02 g of sodium dodecyl sulfate and 0.075 g of PVP, and the pH was adjusted to 9.7, and then 65 nickel oxide powder was added to the system, which was transferred to a reactor, reacted at 170° C. for 10 h, filtered, washed, and dried at 100° C. to obtain a composite powder;
[0032] (3) In an argon atmosphere, the composite powder was kept at 350°C for 2 h and then kept at 1200°C for 2 h;
[0033] (4) The sintered composite powder is subjected to hot isostatic pressing to obtain a nanocrystalline nickel oxide target; wherein the parameters of the hot isostatic pressing treatment are: temperature 1150° C., pressure 1300 MPa, and time 3 h.
[0034] Example 3: A nanocrystalline nickel oxide target material is specifically prepared as follows:
[0035] (1) dissolving 150 g of nickel nitrate hexahydrate in 500 g of deionized water, then adding 0.2 g of hexadecyltrimethylammonium bromide and 1 g of PVP, and adjusting the pH to 10, transferring it to a reactor, reacting it at 180° C. for 12 h, filtering, washing, and drying at 120° C. to obtain nickel oxide powder;
[0036] (2) 15 g of aluminum nitrate nonahydrate was dissolved in 300 g of deionized water, followed by the addition of 0.02 g of sodium dodecyl sulfate and 0.1 g of PVP, and the pH was adjusted to 10, and then 75 g of nickel oxide powder was added to the system, which was transferred to a reactor, reacted at 180° C. for 12 h, filtered, washed, and dried at 120° C. to obtain a composite powder;
[0037] (3) In an argon atmosphere, the composite powder was kept at 400°C for 2 h, and then kept at 1300°C for 2 h;
[0038] (4) The sintered composite powder is subjected to hot isostatic pressing to obtain a nanocrystalline nickel oxide target; wherein the parameters of the hot isostatic pressing treatment are: temperature 1200° C., pressure 1400 MPa, and time 3 h.
[0039] Comparative Example 1:
[0040] (1) 125 g of nickel nitrate hexahydrate and 13 g of aluminum nitrate nonahydrate were dissolved in 400 g of deionized water, followed by adding 0.15 g of hexadecyltrimethylammonium bromide, 0.02 g of sodium dodecyl sulfate and 0.75 g of PVP, and adjusting the pH to 9-10, and transferring the mixture to a reactor, reacting the mixture at 170° C. for 10 h, filtering, washing, and drying the mixture at 80-120° C. to obtain a composite powder;
[0041] (2) In an argon atmosphere, the composite powder was kept at 350°C for 2 h and then kept at 1200°C for 2 h;
[0042] (3) The sintered composite powder is subjected to hot isostatic pressing to obtain a nanocrystalline nickel oxide target; wherein the parameters of the hot isostatic pressing treatment are: temperature 1150° C., pressure 1300 MPa, and time 3 h.
[0043] Comparative Example 2:
[0044] (1) dissolving 125 g of nickel nitrate hexahydrate in 400 g of deionized water, then adding 0.15 g of sodium dodecyl sulfate and 0.75 g of PVP, adjusting the pH to 9-10, transferring the mixture to a reactor, reacting the mixture at 170° C. for 10 h, filtering, washing, and drying the mixture at 80-120° C. to obtain nickel oxide powder;
[0045] (2) 13 g of aluminum nitrate nonahydrate was dissolved in 250 g of deionized water, followed by the addition of 0.02 g of sodium dodecyl sulfate and 0.075 g of PVP, and the pH was adjusted to 9.7, and then 65 nickel oxide powder was added to the system, which was transferred to a reactor, reacted at 170° C. for 10 h, filtered, washed, and dried at 100° C. to obtain a composite powder;
[0046] (3) In an argon atmosphere, the composite powder was kept at 350°C for 2 h and then kept at 1200°C for 2 h;
[0047] (4) The sintered composite powder is subjected to hot isostatic pressing to obtain a nanocrystalline nickel oxide target; wherein the parameters of the hot isostatic pressing treatment are: temperature 1150° C., pressure 1300 MPa, and time 3 h.
[0048] Comparative Example 3:
[0049] (1) dissolving 125 g of nickel nitrate hexahydrate in 400 g of deionized water, then adding 0.15 g of hexadecyltrimethylammonium bromide and 0.75 g of PVP, and adjusting the pH to 9-10, transferring the mixture to a reactor, reacting the mixture at 170° C. for 10 h, filtering, washing, and drying the mixture at 80-120° C. to obtain nickel oxide powder;
[0050] (2) 13 g of aluminum nitrate nonahydrate was dissolved in 250 g of deionized water, followed by the addition of 0.02 g of hexadecyltrimethylammonium bromide and 0.075 g of PVP, and the pH was adjusted to 9.7, and then 65 nickel oxide powder was added to the system, which was transferred to a reactor, reacted at 170° C. for 10 h, filtered, washed, and dried at 100° C. to obtain a composite powder;
[0051] (3) In an argon atmosphere, the composite powder was kept at 350°C for 2 h and then kept at 1200°C for 2 h;
[0052] (4) The sintered composite powder is subjected to hot isostatic pressing to obtain a nanocrystalline nickel oxide target; wherein the parameters of the hot isostatic pressing treatment are: temperature 1150° C., pressure 1300 MPa, and time 3 h.
[0053] Comparative Example 4:
[0054] (1) 125 g of nickel nitrate hexahydrate and 13 g of aluminum nitrate nonahydrate were dissolved in 400 g of deionized water, and then 0.92 g of PVP was added, and the pH was adjusted to 9-10, and the mixture was transferred to a reactor, reacted at 170° C. for 10 h, filtered, washed, and dried at 80-120° C. to obtain a composite powder;
[0055] (2) In an argon atmosphere, the composite powder was kept at 350°C for 2 h and then kept at 1200°C for 2 h;
[0056] (3) The sintered composite powder is subjected to hot isostatic pressing to obtain a nanocrystalline nickel oxide target; wherein the parameters of the hot isostatic pressing treatment are: temperature 1150° C., pressure 1300 MPa, and time 3 h.
[0057] Performance Testing
[0058] Density: The test was conducted according to the Archimedes drainage method. The test results are shown in Table 1.
[0059] Grain size: tested by TEM, the test results are shown in Table 1;
[0060] The samples obtained in the embodiment and the comparative example were subjected to magnetron sputtering, with the glass substrate temperature at 200°C, the power at 100W, the Ar gas flow rate at 50sccm, and the sputtering time at 30min to obtain thin film samples, which were tested as follows:
[0061] Resistivity: tested by four-probe method, the test results are shown in Table 1;
[0062] Light transmittance: measured using a UV-Vis spectrophotometer within a wavelength range of 300-800 nm. The test results are shown in Table 1.
[0063] Table 1 Performance test results
[0064]
[0065] From the data analysis, it can be seen from Examples 1-3 in Table 1 that the nanocrystalline nickel oxide target of the present invention has excellent compactness, which is not less than 97.5%, and the grain size is small, not exceeding 20 nm; and the thin film obtained by sputtering the nanocrystalline nickel oxide target of the present invention has excellent electrical conductivity and transmittance.
[0066] It can be seen from Example 2 and Comparative Example 1 in Table 1 that the present invention first prepares nickel oxide powder by a hydrothermal method, and then uses a hydrothermal method to coat aluminum oxide on the surface of nickel oxide to form a composite powder, so that aluminum oxide is evenly distributed on the surface of nickel oxide powder, which reduces phase separation under high-temperature sintering, improves the uniformity of target grains, and also allows the film obtained after sputtering to have better conductivity and transparency.
[0067] It can be seen from Example 2 and Comparative Examples 2 and 3 in Table 1 that the present invention further improves the uniformity of the target grains by adopting anionic and cationic surfactants, and the electrostatic effect between them enables aluminum oxide to be uniformly and stably adsorbed on the surface of nickel oxide powder, thereby making the film have better conductivity and transparency.
[0068] It can be seen from Example 2 and Comparative Examples 1, 2, 3, and 4 in Table 1 that the present invention adopts a two-step hydrothermal method and a compounding of anionic and cationic surfactants, so that aluminum oxide can be uniformly and stably adsorbed on the surface of nickel oxide powder, thereby reducing phase separation at high temperature and the influence of undesirable phases, and ultimately making the film have excellent conductivity and transparency.
[0069] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
Claims
1. A nanocrystalline nickel oxide target, characterized in that: The method comprises the following preparation steps: (1) dissolving nickel nitrate hexahydrate in deionized water, then adding hexadecyltrimethylammonium bromide and PVP, adjusting the pH to 9-10, transferring it to a reaction kettle, reacting at 160-180° C. for 8-12 hours, filtering, washing, and drying at 80-120° C. to obtain nickel oxide powder; (2) dissolving aluminum nitrate nonahydrate in deionized water, then adding sodium dodecyl sulfate and PVP, and adjusting the pH to 9-10, then adding nickel oxide powder to the system, transferring it to a reactor, reacting at 160-180° C. for 8-12 hours, filtering, washing, and drying at 80-120° C. to obtain a composite powder; (3) Pre-sintering the composite powder in an argon atmosphere, and then keeping the temperature at 1100-1300°C for 2 hours; (4) The sintered composite powder is subjected to hot isostatic pressing to obtain a nanocrystalline nickel oxide target.
2. The nanocrystalline nickel oxide target according to claim 1, characterized in that: The weight ratio of nickel nitrate hexahydrate, deionized water, hexadecyltrimethylammonium bromide and PVP in step (1) is 100-150:300-500:0.1-0.2:0.5-1.
3. The nanocrystalline nickel oxide target according to claim 1, characterized in that: The purity of the nickel nitrate hexahydrate in step (1) is not less than 99.99%.
4. The nanocrystalline nickel oxide target according to claim 1, characterized in that: The weight ratio of aluminum nitrate nonahydrate, deionized water, sodium dodecyl sulfate and PVP in step (2) is 100-150:300-500:0.1-0.2:0.5-1.
5. The nanocrystalline nickel oxide target according to claim 1, characterized in that: The purity of the aluminum nitrate nonahydrate in step (2) is not less than 99.99%.
6. The nanocrystalline nickel oxide target according to claim 1, characterized in that: The weight ratio of nickel nitrate hexahydrate to nickel oxide powder in step (2) is 1:
5.
7. The nanocrystalline nickel oxide target according to claim 1, characterized in that: The pre-sintering temperature in step (3) is 300-400° C. and the time is 2 hours.
8. The nanocrystalline nickel oxide target according to claim 1, characterized in that: The parameters of the hot isostatic pressing treatment in step (4) are: temperature of 1100-1200° C., pressure of 1200-1400 MPa, and time of 2-3 h.
9. The nanocrystalline nickel oxide target according to claim 1, characterized in that: The pH is adjusted by using sodium hydroxide.
10. Use of the nanocrystalline nickel oxide target according to any one of claims 1 to 9, characterized in that: Used to prepare transparent conductive films.
Citation Information
Patent Citations
Nickel-tungsten oxide target and its preparation method
CN110436922B